An investigation into the use of collocations in essay writing among English-majored students: A case study at the selected high schools in Binh Duong province - Du, Tran Thanh; Triet, Au Minh; Thy, Nguyen Le Ngoc (International Journal of Innovative Research and Scientific Studies, 2025)
Collocations, as fixed expressions of word combinations, play a crucial role in enhancing the fluency and accuracy of language production, particularly in essay writing. However, most students, especially high school students, face significant challenges when applying collocations in their essay writing. The current study investigates the use of collocations in essay writing among high school students in Binh Duong Province. Employing a mixed-methods approach, the study combines quantitative analysis of written texts with qualitative data from interview surveys. The quantitative component involved collecting and analyzing a sample of essays written by high school students, focusing on the frequency and correctness of collocation usage and errors. The qualitative aspect provided insights into students’ perceptions, challenges, and strategies regarding collocation usage in their essay writing. The findings reveal a significant variation in the students’ ability to use collocations correctly, with many displaying a limited range of collocational knowledge. This limitation often results in less natural and sometimes awkward expressions in their writing, thereby affecting the overall coherence and quality of their essays. The study also identifies a gap between students’ passive recognition of collocations and their active application in written production. The research concludes that incorporating systematic collocation teaching into the English curriculum could significantly improve students’ writing proficiency, enabling them to produce more native-like and contextually appropriate language. Further exploration should be conducted into the impact of collocation-focused instruction on different aspects of language learning such as developing students’ natural and academic vocabulary knowledge, enhancing their academic writing skills, and improving the fluency of their speaking, with implications for curriculum design and language teaching practices at the tertiary level.